A Survey on Knowledge, Attitude and Practices of Farmers on Management of Rodent Pests (Global Journal of Science Frontier Research, 2014)
A survey on Knowledge, Attitude and Practices (KAP) of 200 farmers on rodent pests and their management was conducted in West Godavari district of Andhra Pradesh, using a structured questionnaire to study the population ecology of rodents, their extent of damage and the various management practices commonly adopted by farmers to control them. The information on this survey is useful to formulate and design the Integrated Rodent Management (IRM) strategies or modules for effective rodent control. Farmers considered rodents as the main biological production constraint in paddy cultivation and estimated that they cause on an average of 10-15% yield losses in every season. Most of the farmers believe that, poison baiting could effectively control rodents, but majority of them were unaware of the dosages of rodenticide ingredients and also unaware of usage of bait stations as the effective rodent control practices. The survey revealed that, most of the farmers are with moderate level of knowledge (68 %) and practices (76 %) and also majority of them were categorized as secondary adopters (81%) basing on the analysis of farmers knowledge, practices and attitude attributes relating to rodent management respectively.
Keywords: KAP analysis; Farmers perceptions; Rodents; Management